Pengaruh Vertical Garden Terhadap Kelembaban Udara Pada Lembar Kerja Siswa Materi Pemanasan Global - Siti Nurjannah; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2019)
This study aims were to determine significant effect of vertical garden toward air humidity on classroom and to find out the characteristics of student worksheet with global warming material in VII grade of junior high school applied using vertical garden. Data were analyzed statistically by independent test. The results showed that there was a significant effect of the used ofvertical garden toward air humidity of the classroom with a significant value of 0,000. While, the results of the validation test for student worksheets which were based on professional validation and practitioner validation had thecategory of